2010
DOI: 10.1111/j.1523-1739.2009.01374.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Diversity of Public Interests in Wildlife Conservation

Abstract: North American state wildlife agencies are increasingly faced with the challenge of effectively representing a diverse public. With increasing social conflict over wildlife issues, the future of wildlife conservation hinges on preparedness of the profession to respond to this challenge. In the interest of finding ways to improve response, 19 agencies in the western U.S. joined forces to initiate an investigation that would provide a better understanding of the diversity of wildlife-related interests in the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
204
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(234 citation statements)
references
References 14 publications
9
204
1
3
Order By: Relevance
“…Indeed, the social sciences have been applied to understand diverse conservation and environmental management problems including, but not limited to, water governance (Armitage et al, 2012;Bakker, 2012;Curran, 2015), fisheries management (Heck et al, 2015;Symes and Hoefnagel, 2010;Wilson et al, 2013), agriculture landscape management (de Snoo et al, 2013), wildlife management (Clark et al, 2008;Gore et al, 2011;Teel and Manfredo, 2010), avian conservation (Kingston, 2016;Veríssimo et al, 2014), protected areas (Brockington and Wilkie, 2015;Ferraro and Pressey, 2015;Lockwood, 2010), forest management (Agrawal and Gupta, 2005;Allen et al, 2014;Ostrom and Nagendra, 2006;Stanturf et al, 2012) and marine conservation planning (Aswani and Hamilton, 2004;Ban et al, 2013;Cornu et al, 2014). The social sciences have also been used to research conservation and environmental management at all scales from local (Bennett et al, 2010) to regional (Pietri et al, 2015) and global (Fleischman et al, 2014).…”
Section: Conservation and The Social Sciencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the social sciences have been applied to understand diverse conservation and environmental management problems including, but not limited to, water governance (Armitage et al, 2012;Bakker, 2012;Curran, 2015), fisheries management (Heck et al, 2015;Symes and Hoefnagel, 2010;Wilson et al, 2013), agriculture landscape management (de Snoo et al, 2013), wildlife management (Clark et al, 2008;Gore et al, 2011;Teel and Manfredo, 2010), avian conservation (Kingston, 2016;Veríssimo et al, 2014), protected areas (Brockington and Wilkie, 2015;Ferraro and Pressey, 2015;Lockwood, 2010), forest management (Agrawal and Gupta, 2005;Allen et al, 2014;Ostrom and Nagendra, 2006;Stanturf et al, 2012) and marine conservation planning (Aswani and Hamilton, 2004;Ban et al, 2013;Cornu et al, 2014). The social sciences have also been used to research conservation and environmental management at all scales from local (Bennett et al, 2010) to regional (Pietri et al, 2015) and global (Fleischman et al, 2014).…”
Section: Conservation and The Social Sciencesmentioning
confidence: 99%
“…Overviews: (Clayton and Myers, 2015;Manfredo, 2008;Saunders, 2003;Vaske and Manfredo, 2012) Examples: (Clayton et al, 2013;Schultz, 2011;Teel and Manfredo, 2010) Environmental Sociology (Sociology)…”
Section: The Social Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have reported that the values of the wider public and government agencies responsible for wildlife management are frequently quite different [9] and that the views of large numbers of people are either ignored or not heard [10], raising the possibility that large numbers of animals are killed or otherwise harmed in ways that would not be approved by the citizens that decision-makers are representing. Studies in Canada reported that the public and experts agreed on potential harm levels, but management strategies that involved killing animals often lacked broad public support [11].…”
Section: Culling Justifications and Calls For More Transparencymentioning
confidence: 99%
“…Given that in many European regions illegal shootings threaten the survival of large carnivore populations (Andrén et al 2006, Červený et al 2002, von Arx et al 2004, Breitenmoser and BreitenmoserWürsten 2008, understanding hunters' perceptions of large carnivores seems especially relevant. Current research on what forms attitudes towards large carnivores includes many quantitative studies that focus on demographic factors, normative beliefs or value orientations (Bath 1989, Bjerke et al 1998, Hunziker et al 2001, Williams et al 2002, Naughton-Treves et al 2003, Kleiven et al 2004, Glikman et al 2010, 2012, Teel and Manfredo 2010, Majic et al 2011, Herrmann et al 2013. With regard to hunters' attitudes these studies arrive at different conclusions.…”
mentioning
confidence: 98%